If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5y + -1) = (-2y + 4) Reorder the terms: (-1 + 5y) = (-2y + 4) Remove parenthesis around (-1 + 5y) -1 + 5y = (-2y + 4) Reorder the terms: -1 + 5y = (4 + -2y) Remove parenthesis around (4 + -2y) -1 + 5y = 4 + -2y Solving -1 + 5y = 4 + -2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '2y' to each side of the equation. -1 + 5y + 2y = 4 + -2y + 2y Combine like terms: 5y + 2y = 7y -1 + 7y = 4 + -2y + 2y Combine like terms: -2y + 2y = 0 -1 + 7y = 4 + 0 -1 + 7y = 4 Add '1' to each side of the equation. -1 + 1 + 7y = 4 + 1 Combine like terms: -1 + 1 = 0 0 + 7y = 4 + 1 7y = 4 + 1 Combine like terms: 4 + 1 = 5 7y = 5 Divide each side by '7'. y = 0.7142857143 Simplifying y = 0.7142857143
| x^2-6x-37=0 | | 0.7(7x+8)=2.7-(x-3) | | 5x+1(-5+2)=18-3 | | 4sqrt(x^2+2x)=4sqrt(3) | | 2x^2-3=x^2+6x | | 5y-7=-169 | | 7n-93=2n-13 | | 4g-3=1g+37 | | X^2+2mx+1=0 | | 23-5n=-3(3-n) | | 17=-7+3n | | x^3-2x=5 | | 9+7=n | | 2*(3x+4)=8*(2x-4) | | (3x^2+x+1)+(2x^2-3x-5)= | | 6z-3=z+7 | | (3y+7)=4 | | 8x+3=-9x-5 | | 6x+131=3x+184 | | 0.75y+9=0.5 | | 4c^3+4c^2-24=0 | | a^2+6a-63=0 | | p(t)=-2t^2+48t+30 | | 9x-3-4x=x+8+x | | 7(2x)-(10-3x)= | | p(t)=-2t+48t+30 | | h=vt-gt | | 6x-2-2x=x+7+x | | 15(-42x-40)=15(-8x+244) | | 8x=2-x^2 | | 6(x-7)+3(x+14)+2(x-15)=-9(x-4)+3(x+7) | | 9-6x=-4x+7 |